Design of Maintenance Service System With Helpdesk It Support Case Smk Bina Am Ma'mur - Pratama, Amri; Padeli, Padeli; Ramadhan, Muhamad Khisbaeni (Journal Collabits, 2024)
SMK Bina Amma'mur has a section in charge of taking care of computers ranging from computer hardware repair and computer software repair, namely the IT helpdesk section. Currently, the process of informing computer repairs that are currently running is still carried out by means of teachers or staff asking for help from the Information Technology department by meeting directly to check problems that occur on computers or laptops, then the IT helpdesk will send a team of technicians to solve the reported problems, if it has been completed, it will be reported back to the IT helpdesk to note that computer repair requests have been made. After checking the problem that occurs on the computer or laptop then the IT department will record the problem in the general ledger and will notify the teacher or staff when it has been resolved via whatsapp media. However, the handling of problems that are running is still not good because the process of recording repair results is still manual so that it affects the performance of the IT department. This can have a negative impact, namely there are problems recording data repeatedly, the process of searching for computer repair data takes a long time because you have to search one by one for repair request data in books, there are often errors in making reports so that the reports made are not the same as the computer repair process. This research resulted in an IT helpdesk system that aims to help the IT department manage IT helpdesk data better. This research uses the PIECES analysis method, design using UML and blackbox testing system. The IT Helpdesk system is created using PHP programming language and MySQL database.